2021
DOI: 10.1177/15347354211000119
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Wedelia chinensis on Human Glioblastoma Multiforme Cells

Abstract: Introduction: Glioblastoma multiforme (GBM) is the most aggressive glioma, and its diffuse nature makes resection of it difficult. Moreover, even with the administration of postoperative radiotherapy and chemotherapy, prolonged remission is often not achieved. Hence, innovative or alternative treatments for GBM are urgently required. Traditional Chinese herbs and their functional components have long been used in the treatment of various cancers, including GBM. The current study investigated the antitumor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…(Birzu et al, 2020). In addition, the current first‐line treatments for GBM can almost not effectively prolong survival, so there is an urgent need for new therapeutic approaches and new therapeutic agents for GBM (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(Birzu et al, 2020). In addition, the current first‐line treatments for GBM can almost not effectively prolong survival, so there is an urgent need for new therapeutic approaches and new therapeutic agents for GBM (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin regulates the autophagy activities by increasing the LC3II/I ratio and expressions of Atg-7, Atg-5 and beclin-1 levels and decreasing p62 levels in U87-MG cells [ 87 ]. Apigenin also enhanced PARP cleavage at 40 and 80 μM, with the indication of loss of DNA repair and G2/M cell cycle arrest [ 24 ].…”
Section: Flavonoids and The Mechanism Of Action Against High-grade Ad...mentioning
confidence: 99%
“…Several compounds including flavonoids, diterpenes, triterpene saponins, and phytosteroids were reported in this extract. Recently extensive studies have demonstrated the anti-cancer properties of WCE against prostate, lung, breast, colon, glioblastoma, and pancreatic cancer cells [25].…”
Section: Data Collectionmentioning
confidence: 99%